Pertimbangan Hakim dalam Mengabulkan Dispensasi Nikah - Laila, Dwi Mei; Hanifah, Shofia; Izzaba, Nabila; Zaskia, Tsabita (Indonesian Journal of Law and Justice, 2023)
: Early marriage is the marriage of a couple who is still young, that is, they have not reached the age of 20 years. The impact of early marriage is to increase the risk of health problems for both mother and child. Many cases are kept in the Religious Courts, especially those related to the timing of marriage. It is impossible for a judge to reject a case he is hearing, let alone a marriage case itself. Marriage is the right to enter into a marriage granted by a religious court in the form of law. This freedom is offered by someone who is about to get married but whose age does not yet meet the requirements of the Marriage Law in Article 7 paragraph (2) of Law Number 1 of 1974. Regarding marriage, its meaning is not determined by reflection, therefore in this case the judge is obliged to determine The content of the article itself determines the request for marriage freedom that is granted. The purpose of this research is to find out how judges decide divorce cases? This type of research is descriptive research, where the author made this research, the source is from many references. From the research results, it can be concluded that Religious Court Judges determine the freedom to marry in accordance with existing regulations.